2021
DOI: 10.2478/johr-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Light Intensity and CO2 Concentration Alters Biomass Partitioning in Chrysanthemum

Abstract: Biomass partitioning is one of the pivotal determinants of crop growth management, which is influenced by environmental cues. Light and CO2 are the main drivers of photosynthesis and biomass production in plants. In this study, the effects of CO2 levels: ambient 400 ppm (a[CO2]) and elevated to 1,000 ppm (e[CO2]) and different light intensities (75, 150, 300, 600 μmol·m−2·s−1 photosynthetic photon flux density – PPFD) were studied on the growth, yield, and biomass partitioning in chrysanthemum plants. The plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(61 reference statements)
2
3
0
Order By: Relevance
“…This circumstance elaborates on the underlying mechanism through which PPFD compensated for N uptake under N constraint. Concurred with our results, the positive effect of PPFD on root biomass reported on lettuce 14 and chrysanthemum 41 . Regardless of PPFD, increase in N concentration reduced the partitioning of biomass to flowers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This circumstance elaborates on the underlying mechanism through which PPFD compensated for N uptake under N constraint. Concurred with our results, the positive effect of PPFD on root biomass reported on lettuce 14 and chrysanthemum 41 . Regardless of PPFD, increase in N concentration reduced the partitioning of biomass to flowers.…”
Section: Discussionsupporting
confidence: 89%
“…We observed that the adverse effects of nitrogen deficiency extended to the reproductive growth stage and eventually prolonged the flower emergence period and decreased the biomass partitioning to the flower under low PPFD The positive role of PPFD on the flower emergence period and the increasing number of flowers have been also declared in the previous study on chrysanthemum 41 . In addition, a strong genetic correlation between flowering date and NUE has been reported in wheat 42 .…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the optimum growth light intensity for light use efficiency was clearly the 300 µmol m −2 s −1 PPFD. In lettuce, the optimum growth light intensity was 600 µmol m −2 s −1 PPFD 16,17,[41][42][43][44] , while for Aloe vera L. it was 50% of sunlight as compared to 75 or 100% 44 . F v /F m was generally not affected by TiO 2 nanoparticle spray, except for an increase noted at 75 µmol m −2 s −1 PPFD.…”
Section: Discussionmentioning
confidence: 99%
“…Light quality can potentially change the allocation of biomass toward the aboveground or underground parts of the plant [ 28 , 29 ]. In the present study, B and R lights caused a contrasting pattern of biomass partitioning into the above- or under-ground parts of the chrysanthemum rooted cuttings.…”
Section: Discussionmentioning
confidence: 99%